Understanding specific gender dynamics in the cowpea value chain for key traits to inform cowpea breeding programs in Malawi, Mozambique and Tanzania - Chipeta, Michael M.; Kampanje-Phiri, Jessica; Moyo, Dumisani; Colial, Henriques; Tamba, Mussa; Belarmino, Divage; Hella, Joseph; Yohane, Esnart; Mvula, Naomi; Kafwambira, John (Frontiers in Sociology, 2024)
Cowpea is an important food and nutrition security crop in Malawi, Mozambique and Tanzania and it is mainly produced by women farmers mainly on a subsistence scale. The majority of these farmers use local varieties despite the availability of improved varieties in the region. Low acceptability and adoption of improved varieties have also hampered cowpea breeding efforts. The low adoption, especially among women farmers, has been attributed to the failure by breeding programs to involve farmers in the process of designing and developing improved varieties with a view to meeting their priorities and preferences. Despite women constituting the majority of cowpea farmers in these countries, no comprehensive gender analysis on cowpea value chain had been instituted to understand the traits that are gender and youth responsive and how to incorporate them in the product profiling so that the developed varieties benefit men, women and youth. The main objective of the gender study was, therefore, to identify preferred traits by different gender groups within the whole cowpea value chain to inform cowpea breeding programs in the three countries. The study employed quantitative and qualitative methods to elucidate preferences, including value chain mapping, a quantitative survey of farmers, focus group discussions and key informant interviews targeting farmers/consumers, traders, policymakers and processors. Results of the gender study has had two major influences on our cowpea breeding program: firstly, the breeding program changed the way it prioritizes traits to include ones that reflect the needs of men, women and the youth in the cowpea value chain. Secondly, our breeding objectives are closely aligned to gender differences in the target population of farmers and other users, by incorporating key priority traits that address the needs of both men and women, including the youth. That is to say, product targets and specific product profiles are more gender sensitive. Since the breeding work is ongoing, the expectation is that the development of improved varieties resulting from this gender sensitive process will translate into higher adoption levels of these varieties (compared with previous releases), which might have ripple effects on food, nutrition and income security in the region.